Effects of protein digestion on in vitro digestibility of starch in sorghum differing in endosperm hardness and flour particle size. (30th July 2022) - Xu, Xiaoli; Bean, Scott; Wu, Xiaorong; Shi, Yong-Cheng
Highlights: Digestibility of sorghum starch was affected by degree of protein digestion. Pepsin treatment significantly increased sorghum starch digestibility. The pH value (2.0 vs. 1.3) was a critical factor affecting protein digestion. Sorghum flour had higher RS contents than isolated sorghum starch. Endosperm hardness showed no obvious trend on starch digestibility. Abstract: In vitro digestibility of starch in sorghum grains differing in endosperm hardness and flour particle size was investigated. The starch digestibility increased as the particle size of flour decreased, but no clear trend was observed in digestibility of starch in sorghum flours milled from grains with different hardness. The protein matrix affected the digestion of starch. The pH value (2.0 vs. 1.3) was a critical factor affecting protein digestion. Optimum pH (pH 2.0 for pepsin) digested more protein, resulting in a greater digestion of starch. Resistant starch (RS) content was 8.5–26.3% in isolated sorghum starch but higher (10.6–29.5%) in sorghum flours. Protein digestibility decreased after cooking while starch digestibility increased compared to native sorghum flours; disulfide bonds formed between protein molecules. RS content of cooked sorghum flour was much higher without pepsin treatment (16.93–23.99%) than that of cooked sorghum flour with pepsin treatment (4.86–12.53%).